Images and memory: religiosity and sacrifice – the cases of Tierralta, Trujillo and Arenillo in Colombia - Guerrero, Freddy A. (International journal of transitional justice, 2020)
Memory in Colombia is a human right that is recognized for victims and society in the framework of processes of transitional justice, and in the last decade there has been an institutionalization of memory, with organizations arising whose purpose is to manage memory initiatives in the country. However, organizational and community memory and denunciation processes and practices have been developed, materialized and represented through objects/images, like sources and references for memory aimed to account for the atrocious past and promote acts of resistance and humanity amid the inhumanity of war. From a fragmentary perspective, we concentrate on three cases of images in Colombia that, based on religious and cultural representations, allow us to observe their power in processes of recovering memory, of denunciation and demands with regard to respect for human rights.